Down Payment Refund Clauses in Non-Cash Home Purchases (Taqsit): A Murabaḥah-Based Assessment of Gharar at PT Hadrah Aceh Pratama - Fiona Nurul Hida Hunaifi; Muhammad Siddiq Armia; Ida Friatna (Lembaga Aneuk Muda Peduli Umat, Bekerjasama dengan LaKaspia, 2025)
This study examines the application of a murābaḥah framework in non-cash home purchases (taqsīṭ) at PT Hadrah Aceh Pratama, with particular attention to price disclosure and the down payment refund clause when a bank rejects a buyer’s financing application. Using a normative–empirical design, the analysis integrates doctrinal standards from fiqh al-muʿāmalah and DSN–MUI Fatwa No. 04/DSN-MUI/IV/2000 with field evidence drawn from written contracts, supporting transaction documents, observations, and interviews conducted on 25 October 2024 and 15 September 2025. The contracts set out the base cost, the agreed margin, and the installment schedule, while the down payment is determined by unit type. The central issue concerns the refund mechanism. The contract makes the refund contingent on the resale of the unit and does not stipulate a definite deadline. Although interviews indicate an internal target timeframe, the written clause leaves the time of performance open. This creates uncertainty (gharar) and falls short of the requirement of clarity (bayān) regarding obligations and timing in a valid murābaḥah arrangement. The study recommends that the contract specify a clear refund deadline independent of resale, provide a straightforward procedure for failed transactions, and state related fees in precise and transparent terms to protect both parties and support justice within the aims of maqāṣid al-sharīʿah.